Tragedi 13 Mei 1969 dalam Berbagai Perspektif - Muhammad Hasmi Yanuardi; Ahmad Musyalen Firdaus (Program Studi Pendidikan Sejarah Pascasarjana UNJ, 2023)
The purpose of this study is to describe the May 13, 1969 Tragedy according to various existing perspectives. The method used in writing this article uses stages that are usually standard in historical research, such as starting from selecting topics, gathering sources, verifying which contains historical criticism and the validity of sources, then proceeding to the interpretation stage and ending with writing. The results of this study are that the May 13, 1969 Tragedy was an event of racial riots between ethnic Malays and ethnic Chinese in Malaysia, especially in Kuala Lumpur, Selangor. The incident which was the result of the Opposition Party's victory march consisting of the Malaysian People's Movement Party (Parti Gerakan) and the Democratic Action Party (DAP) resulted in riots that paralyzed the country. In understanding this event, there are several perspectives such as originating from the Official Sources of the Malaysian Government, the existence of provocation by the Communist group, the Government's failure to prosper the Malay ethnicity and the dynamics of Sino-Malay social and economic interaction. From several existing perspectives, it cannot be decided that the cause of the May 13, 1969 Tragedy was only due to a single cause but could also be caused by various triggering factors. These factors can be in the form of socio-economic inequality, political rivalry and security threats from communist groups. Tujuan dari penelitian ini adalah untuk mendeskripsikan Tragedi 13 Mei 1969 menurut berbagai perspektif yang ada. Metode yang digunakan dalam penulisan artikel ini menggunakan tahapan-tahapan yang lazimnya menjadi standard dalam penelitian sejarah seperti diawali dari pemilihan topik, pengumpulan sumber, verifikasi yang di dalamnya memuat atas kritik sejarah dan keabsahan sumber, kemudian dilanjutkan pada tahap interpretasi dan diakhiri dengan penulisan. Hasil penelitian ini adalah Tragedi 13 Mei 1969 merupakan peristiwa kerusuhan rasial antara etnis Melayu dengan etnis Tionghoa di Malaysia, khususnya di Kuala Lumpur, Selangor. Peristiwa yang merupakan dampak pawai kemenangan Partai Oposisi yang terdiri dari Parti Gerakan Rakyat Malaysia (Parti Gerakan) dan Democratic Action Party (DAP) mengakibatkan kerusuhan hingga melumpuhkan negara. Di dalam memahami peristiwa ini, terdapat beberapa perspektif seperti berasal dari Sumber Resmi Pemerintah Malaysia, adanya provokasi kelompok Komunis, Kegagalan Pemerintah dalam mensejahterakan etnis Melayu dan dinamika interaksi sosial dan ekonomi Sino-Melayu. Dari beberapa perspektif yang ada, tidak dapat diputuskan bahwa penyebab Tragedi 13 Mei 1969 hanya karena sebab tunggal tetapi dapat disebabkan juga dari berbagai faktor yang memicu. Faktor tersebut dapat berupa ketimpangan sosial-ekonomi, rivalitas politik dan ancaman keamanan dari kelompok komunis.